PENGARUH TEKNIK RELAKSASI NAFAS DALAM TRHADAP RESPON NYERI PADA IBU INPARTU KALA I FASE AKTIF DI PUSKESMAS BAHU KOTA MANADO - Novita, Kalalo Ribka; Rompas, Sefti; Bataha, Yolanda B. (JURNAL KEPERAWATAN, 2017)
Abstract : A pregnant mother’s pain scale at the first stage of the active phase of the average are inmoderate to severe pain. Labor pain can be controlled by two methods, pharmacological and nonpharmacological technique. In the pharmacological methods there are various methods, one of themis with deep breathing relaxation techniques. The purpose of this study is to see if deep breathingrelaxation techniques on pain influences the pregnant mother’s active phase of the first stage atPuskesmas (Community Health Center) Bahu, City of Manado. This research design used is preexperiment with one group pretest-post design. The sampling technique used is an accidentalsampling with a total 26 samples. The result of statistical tests T-test with a credible level of 95%(α=0,05) and obtained 0,000 p value <0,05. The conclusion is deep breathing relaxation techniqueson pain does have an influence on the pregnant mother’s active phase of the first stage in Puskesmas(Community Health Center) Bahu, City of Manado. The suggestion of this study are expected toprovide a reference for the development of independent intervention of nurse in non-pharmacologicalpain management.Keyword : Pregnant Mother’s First Active Phase, Pain, DeepBreathing Relaxation TechniquesAbstrak : Skala nyeri pada ibu inpartu kala I fase aktif rata-rata berada pada skala nyeri sedanghingga berat terkontrol. Nyeri persalinan dapat dikendalikan dengan dua metode yaitu farmakologisdan non farmakologis. Pada metode non farmakologis terdapat berbagai metode, salah satunyadengan teknik relaksasi nafas dalam. Tujuan Penelitian mengetahui pengaruh teknik relaksasi nafasdalam terhadap respon nyeri pada ibu inpartu kala I fase aktif di Puskesmas Bahu Kota Manado.Desain Penelitian ini menggunakan pra eksperimen dengan pendekatan one group pretest-postdesign.. Teknik pengambilan Sampel menggunakan accidental sampling dengan jumlah sampelsebanyak 26 orang. Hasil Uji Statistik Wilcoxon signed rank test dengan tingkat kepercayaan 95%(α=0,05) dan diperoleh p value 0,000 < 0,05. Kesimpulan yaitu adanya Pengaruh Teknik RelaksasiNafas Dalam Terhadap Respon Nyeri Pada Ibu Inpartu Kala I Fase Aktif di Puskesmas Bahu KotaManado. Saran penelitian ini diharapkan dapat memberikan referensi bagi perkembangan intervensimandiri perawat dalam manajemen nyeri non farmakologi.Kata kunci : Ibu Inpartu Kala I Fase aktif, Nyeri, TeknikRelaksasi Nafas Dalam